Círculo de cultura com adolescentes a grupos religiosos e a prevenção do HIV/AIDS - Ferreira, Adriana Gomes Nogueira (2010)
Prevention is an effective means for working with HIV / AIDS and the church as a network of community health is a setting conducive to the cultural construction of adolescents with regard to the adoption of safe sexual behaviors, it adopts cautious to demonstrate the value of sex with responsibility and especially with respect to self and other. The study has as main objective to promote a critical and reflective area facing the HIV / AIDS with teens who are part of a group of the Catholic Church in the city of Tianguá-Ceará, based on the thought of Paulo Freire. This is a research- action, carried out between May and August 2009. The subjects were ten adolescents placed in youth groups of Catholic Charismatic Renewal. The instruments for data collection used a form of interview, participant observation, photographic records, filming and recording in the field diary. As the method and technique were used Circles of Culture to articulate the collective dimension of interactive research in the development of action research. Thus were carried out eight circles of culture constructed in accordance with the following steps: discovery of the Universe individual and collective problematization and theory, deconstruction of theoretical concepts and practice, collective (re) construction, summary of the experience, evaluation of each circle and one final assessment for these periods was necessary to select the themes and creating situations for questioning in accordance with the perceived reality. The circles considered the assumptions of the Paulo Freire method, such as: dialogue, participation, theoretical and practical value of knowledge, respect for culture, access to content relating to the reality and autonomy to carry out choices based on critical reflection of the reality . The analysis and interpretation of results have concentrated on the discussion of the data, according to the sequence of circles considering the experience of the group and the dialogue with the literature carried out by the researcher. In this sense the adolescents reflected on the themes: HIV / AIDS, chastity, sexuality and prevention in the religious context, moments that led to the deconstruction and (re) construction of concepts and (pre) concepts. The completion of the circle of culture as educational and investigative strategy with adolescents from the church is awakening to the influence that the church plays in this group when its teachings are related to teaching of the chastity and fidelity understood as behaviors to be adopted and the resulting means of preventing HIV / AIDS , the silencing of the church about sexuality, the devaluation of information on condom use by adolescents and recognition of the need for more knowledge that address the issues that emerged in the study. Therefore nurses need to use methodologies that promote emancipatory dialogue founded on the trust and respect between teacher / student, strengthening a relationship of friendship to the reflection about the adoption of safe sexual behaviors in adolescents in the church.